2010
DOI: 10.3109/09537100903521611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended release niacin/laropiprant, laropiprant, extended release niacin and placebo on platelet aggregation and bleeding time in healthy subjects

Abstract: Laropiprant (LRPT) has been shown to reduce flushing symptoms induced by niacin and has been combined with niacin for treatment of dyslipidemia. LRPT, a potent PGD(2) receptor (DP1) antagonist that also has modest activity at the thromboxane receptor (TP), may have the potential to alter platelet function either by enhancing platelet reactivity through DP1 antagonism or by inhibiting platelet aggregation through TP antagonism. Studies of platelet aggregation ex vivo and bleeding time have shown that LRPT, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
1
20
2
Order By: Relevance
“…It has been speculated that antagonism of DP1 could block the ability of endogenous PGD 2 to inhibit further platelet aggregation and thereby may indirectly enhance the reactivity of platelets. However, several clinical studies have indicated that treatment with the DP1 antagonist laropiprant has no platelet-aggregatory effect; in fact, a transient and mild increase in bleeding time has been reported (32)(33)(34). One caveat in interpreting this observation is that laropiprant has been shown to antagonize both DP1 and TP in humans (32)(33)(34), unlike the DP1-specifi c antagonist L-655 used in this mouse work.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…It has been speculated that antagonism of DP1 could block the ability of endogenous PGD 2 to inhibit further platelet aggregation and thereby may indirectly enhance the reactivity of platelets. However, several clinical studies have indicated that treatment with the DP1 antagonist laropiprant has no platelet-aggregatory effect; in fact, a transient and mild increase in bleeding time has been reported (32)(33)(34). One caveat in interpreting this observation is that laropiprant has been shown to antagonize both DP1 and TP in humans (32)(33)(34), unlike the DP1-specifi c antagonist L-655 used in this mouse work.…”
Section: Discussioncontrasting
confidence: 43%
“…However, several clinical studies have indicated that treatment with the DP1 antagonist laropiprant has no platelet-aggregatory effect; in fact, a transient and mild increase in bleeding time has been reported (32)(33)(34). One caveat in interpreting this observation is that laropiprant has been shown to antagonize both DP1 and TP in humans (32)(33)(34), unlike the DP1-specifi c antagonist L-655 used in this mouse work. Therefore, it is likely that the mild anti-platelet effects in humans are a result of TP antagonism and theoretically represent a net effect of antagonizing both DP1 and TP on platelets.…”
Section: Discussioncontrasting
confidence: 43%
“…The same patient may appear in more than one category. volunteers, using a highly sensitive ex vivo method [12]. The results demonstrated that the platelet aggregation in response to increasing concentrations of collagen at 24 hours post-dose on day 7 was similar following treatment with either extended release nicotinic acid/laropiprant or extended release nicotinic acid alone [12].…”
Section: Discussionmentioning
confidence: 95%
“…volunteers, using a highly sensitive ex vivo method [12]. The results demonstrated that the platelet aggregation in response to increasing concentrations of collagen at 24 hours post-dose on day 7 was similar following treatment with either extended release nicotinic acid/laropiprant or extended release nicotinic acid alone [12]. At 2 hours post-dose on day 7, the EC 50 for collagen-induced platelet aggregation was $2-fold higher in the presence of laropiprant, suggesting an effect of laropiprant to inhibit platelet responsiveness to collagen [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation